Brain Metastases from Cervical Cancer – a Short Review. Issue 5 (September 2014) - Branch, Byron C; Henry, James; Vecil, Giacomo G
Aims and Background: Brain metastases from cervical cancer are extremely rare yet local recurrence and systemic spread is fairly common. The role of surgical resection and CNS screening for this pathology was interrogated from a review of the literature. Clinical Experience: We present a case of a single brain metastasis that originated from the cervix and describe chronologically the spread of the disease with pathological confirmations. Review: Following an extensive English literature search, which only yielded 59 reported cases (n = 60 including the present case), we extrapolated basic trends regarding the demographics, pathophysiology, and treatment that portended a longer survival. Despite treatment, the majority of patients do not survive past 1 year from diagnosis of intracranial metastasis. A trend towards prolonged survival was observed among patients who received surgical resection of the brain metastasis. Conclusions: Cervical carcinoma has been documented to metastasize to the brain, and this may occur via initial seeding of the lungs. Surgical resection and CNS screening may have beneficial roles in the management of metastatic cervical carcinoma.